Understanding family caregiving and well-being in adult chronic illness: a call for a more comprehensive perspective - Schwind, Bettina; Visscher, Rosa; Haslbeck, Jörg; Falkenstein, Thomas; Riewoldt, Christina; Griese, Lennert; Behrisch, Birgit; Metzing, Sabine; Nagl-Cupal, Martin (Frontiers in Public Health, 2025)
The rising burden of chronic illness, driven by increased life expectancy and an aging population, has amplified the demand for family caregiving and research thereof to assure the well-being of families in the future. Addressing these challenges requires an evaluation of the existing gaps in research on family caregiving and well-being in adult chronic illness. In order to achieve this, seven scholars from various academic disciplines who are researching this topic in Austria, Germany, and Switzerland convened for a two-day workshop in 2024. Discussions were complemented by a set of initial literature searches. The workshop revealed that studies documenting the burdens of informal caregiving have tended to overlook the broader family and social contexts, as well as the well-being of families as a whole, by focusing on single perspectives and improvement of disease management. Thereby, current research fails to address the diverse needs of all family members involved and often neglects intertwined factors like gender, socioeconomic status, and access to the formal health and care system. This results in gaps in how these intertwined factors influence family caregiving and well-being. We propose a more comprehensive, interdisciplinary investigation of family caregiving and well-being in future studies. Further scientific consideration is needed to adequately address the structural and procedural barriers to (in)formal support for families. Understanding the real-life complexities of caregiving can contribute to bridging gaps in research and practice, while promoting family-centered approaches to contribute to health equity. Research and practice recommendations are provided.